2022
DOI: 10.1111/pbr.13024
|View full text |Cite
|
Sign up to set email alerts
|

Development of a near‐infrared spectroscopy calibration for Hagberg falling number assessment of barley (Hordeum vulgare): A comparison of methods

Abstract: Climate change leads to increased risks of reduced Hagberg falling numbers (HFN).The objectives of this study were to (i) compare partial least square (PLS) with deep learning methods with respect to establishing near-infrared spectroscopy (NIRS) calibrations for HFN in spring barley, (ii) compare the accuracy of NIRS calibrations for metric versus categorical response variables and (iii) discuss the usefulness of the developed NIRS calibrations in the context of barley breeding programmes. This study was base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…Parameter estimates based on the calibration dataset demonstrated that the best model was PLSR, outperforming Bayesian and PCA‐ANN models (Table 4) likely due to its ability to handle multicollinearity in our spectral data. The superiority of the PLSR model compared to other advanced models is consistent with earlier works, with the PLSR model outperforming ANN and GBM regression deployed in the rapid detection of the microbial spoilage of beef fillets, 26 rapid determination of moisture content in rubber sheets, 27 and the prediction of Hagberg's falling number in barley 28 . This has been attributed to a linear relationship between the spectral data (predictors) and reference data 29 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Parameter estimates based on the calibration dataset demonstrated that the best model was PLSR, outperforming Bayesian and PCA‐ANN models (Table 4) likely due to its ability to handle multicollinearity in our spectral data. The superiority of the PLSR model compared to other advanced models is consistent with earlier works, with the PLSR model outperforming ANN and GBM regression deployed in the rapid detection of the microbial spoilage of beef fillets, 26 rapid determination of moisture content in rubber sheets, 27 and the prediction of Hagberg's falling number in barley 28 . This has been attributed to a linear relationship between the spectral data (predictors) and reference data 29 .…”
Section: Discussionsupporting
confidence: 82%
“…If this is achieved, a “walk back” approach can be used to select superior barley lines using the developed barley malt NIR spectroscopy calibration as a “proxy,” an idea we are currently exploring. We suspected that the high predictive ability obtained for WP compared to the rest of the malt quality traits may have been influenced by the sensitivity of the NIR spectral data to proteins, especially seed storage proteins 28 . NIR spectroscopy is based on measurements arising from inter‐atomic bonds between atoms of low mass such as C, N, O, and H. Although it is more sensitive to proteins through a conglomeration of the N‐H bond vibrations, the sensitivity of the NIR response to individual amino acids is quite challenging 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations